2004
DOI: 10.14314/polimery.2004.641
|View full text |Cite
|
Sign up to set email alerts
|

Silica powder obtained by sol-gel method as a support of organometallic vanadium catalyst for ethylene polymerization

Abstract: lUM-7l oG' H ' ', łm.'ccz,Ą],Ą '\AT^lI^\U'KoVĄlF\A Silica powder obtained bysol-8el metho.l as a support of ortanometalli. vanadium catalyst for ethylene polymerization RAPID COMMUNICATION sumnary Sol gcltc.hniquc was enployed roobbin thc s ili.i,iy p. pow d.i vhich aftcl nrodjfi.iiion proredure was aPPlicd a suppoł 01Ór ganondi]li. c ilyiic syśen for rdlylĆne polyń iz iol Tlt powds PrG dud lvis synlhcsju.d usins hydblysis ańd condcnsation 01TEos, rhl],zcd by mmoi.' obbin€ d młłial and a Ęfer.Dc suPpolt (.omne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…That decrease of the titanium loading may be attributed to the presence of methyl group. It was observed earlier for the VOCl 3 catalyst immobilized on silica type sol‐gel carriers that the vanadium content in the catalyst dropped down after the carriers were used which contain methyl groups 12(c). The reduced share of the complex in the course of synthesis results in lower amounts of immobilized titanium (Table 2), irrespective of the type of the carrier used.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…That decrease of the titanium loading may be attributed to the presence of methyl group. It was observed earlier for the VOCl 3 catalyst immobilized on silica type sol‐gel carriers that the vanadium content in the catalyst dropped down after the carriers were used which contain methyl groups 12(c). The reduced share of the complex in the course of synthesis results in lower amounts of immobilized titanium (Table 2), irrespective of the type of the carrier used.…”
Section: Resultsmentioning
confidence: 86%
“…The difference in the latter results predominantly from the types of precursors which were used in their synthesis; TEOS was used for the synthesis of SG and powders SG 0.2Me and SG 0.8Me were obtained by the replacement of 20 or 80%, respectively, of TEOS with methyltriethoxysilicate (Table 1). The use of a precursor with a nonhydrolyzing SiC bond allows for the chemical modification of the surface which gives materials having methyl groups in addition to hydroxyl groups 12(b)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was selected because our earlier ethylene homopolymerisation studies revealed that such materials improved the activity of the catalytic system. [28] The silica-type sol-gel product, with no previous modification by the organoaluminium compound, was used directly in the synthesis of heterogeneous metallocene catalysts. The amount of zirconium anchored to its surface turned out to be nearly the same as that deposited on MgCl 2 (MeOH) 6 and higher than the amount of zirconium anchored to the magnesium chloride and tetrahydrofuran complex (Table 1).…”
Section: Resultsmentioning
confidence: 99%